2013
DOI: 10.1093/icvts/ivs564
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant surgical atrial fibrillation ablation and event recorder implantation: better monitoring, better outcome?

Abstract: Implantation of an ER with link-up to a cardiology and/or electrophysiology provides optimized anti-arrhythmic drug management and higher rates of consecutive procedures like cardioversion or additional catheter-based ablation. As a result, a trend to higher sinus rhythm conversion rate was observed after 1-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[ 56 ] TAVR, and to a greater degree SAVR, carries a risk of developing NOAF. [ 57 , 58 ] This arrhythmia has significant health, economic, and clinical implications, because the length of hospital stay and the risk of stroke and mortality are increased. [ 59 ] Future studies identifying predictive factors for postprocedural NOAF will help in selecting high-risk patients who might benefit from prophylactic antiarrhythmic therapy or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] TAVR, and to a greater degree SAVR, carries a risk of developing NOAF. [ 57 , 58 ] This arrhythmia has significant health, economic, and clinical implications, because the length of hospital stay and the risk of stroke and mortality are increased. [ 59 ] Future studies identifying predictive factors for postprocedural NOAF will help in selecting high-risk patients who might benefit from prophylactic antiarrhythmic therapy or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…More intensive monitoring is associated with a greater likelihood of detecting both symptomatic and asymptomatic AF. 57 , 414 , 937 , 938 , 939 , 940 , 941 , 942 , 943 , 944 The proportion of asymptomatic compared with symptomatic events might be higher after AF ablation; two studies reported that the proportion of AF events that were asymptomatic was 11%–35% prior to and 53%–65% after ablation. 63 , 945 , 946 Another study reported that for patients in sinus rhythm, 53.8% of AF episodes were asymptomatic, with an increase in asymptomatic episodes changing from the acute to the chronic period after ablation, demonstrating that AF success cannot be based on the absence of symptoms alone.…”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
“…In one study after concomitant surgical ablation, ILRs compared with conventional Holter monitoring facilitated more follow-up antiarrhythmic management, including cardioversions and catheter ablation procedures, which were associated with a trend toward higher sinus rhythm rates at 1 year. 942 …”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
“…11 Some studies have used postoperative continuous monitoring, either invasive or noninvasive, to follow up patients. 12,13 Continuous monitoring allows a higher degree of confidence in detecting the real incidence of sinus rhythm recovery and occurrence of transient attacks of arrhythmias, compared to the interval monitoring used in our study. Unfortunately, such modalities of monitoring were not available in our center during our study.…”
Section: Discussionmentioning
confidence: 95%